Salivation quantum – stomatopyrosis : autogenic training - Gruden-Pokupec, Josipa-Sanja (Array, 2009)
Abstract: Stomatopyrosis of 'burning mouth' syndrome, in a narrower sense of definition, is a condition characterized by sensation of burning and heating in mouth, despite its normal mucosa. This research has been directed towards treatment of stomatopyrosis, putting emphasis on the implementation of psychopharmacotherapy and psychotherapy. The research was conducted on altogether 120 respondents suffering from stomatopyrosis. The respondents were divided into two equal groups: each one comprising 60 members. All the respondents were treated by means of a standard topical therapy. All the patients were assessed clinically and by means of psychological tests measuring depression and anxiety four times: once before the treatment, after one month, after two months and after four months since the beginning of the treatment. The acquired data were afterwards statistically processed. When grading the symptoms on VAS, i.e. visual analogous scale, the subjective assessment of symptoms was marked as 7–8 cm, which shows a high degree of burning sensation. According to our study, the quantity of saliva, which was at the beginning of the research slightly decreased, normalized after the treatment. Apart from the clinical investigation of stomatopyrosis, we applied Depression and Anxiety questionnaires. On the basis of our research, we have concluded the following: the comorbidity of stomatopyrosis with the phenomena of anxiety and depression proves that, among other factors, there is a psychogenic aetiology of this disease. Autogenic training, which is a psychotherapeutic anxiolytic technique, is a therapy of choice for stomatopyrosis, which contributes not only to the elimination of oral complaints, but to the emotional rehabilitation of the patients as well, and to the reduction of dryness in the mouth.